A novel perylene-bisimide dye as "turn on" fluorescent sensor for Hg2+ ion found in DMF/H2O. (February 2015) - Malkondu, Sait; Erdemir, Serkan
Abstract: A highly efficient and selective perylene-bisimide sensor bearing thiophene units as the metal ion receptor is reported for the detection of Hg 2+ ion. This sensor displays a rapid and highly selective "turn–on" response based on photoinduced electron transfer (PET) mechanism. Fluorescence enhancement by factors 20 times is achieved upon selective interaction with Hg 2+ ion over other metal ions in aqueous solutions. Graphical abstract: Highlights: A novel perylene-bisimide dye (PETTA ) bearing thiophene units were synthesized in two steps. The preparedPETTA was characterized by using spectroscopic techniques. PETTA displayed a rapid and highly selective "turn–on" response towards Hg 2+ ion in DMF/H2 O.